Dame Kathleen Kenyon: digging up the Holy Land - Davis, Miriam C. (Publications of the Institute of Archaeology, University College London, 2008)
In the shadow of the British Museum -- Beginning in archaeology -- From St. Albans to Samaria -- The Institute of Archaeology -- Walls of Jericho -- "The oldest town in the world" -- Searching for the City of David -- Battling over Jerusalem -- St. Hugh's and Rose Hill